Electrical instability of the myocardium in children of different ages: diagnosis, prognostic significance and principles of correction (literature review) - Larisa A. Balykova; Denis O. Vladimirov; Evgenia N. Tyagusheva; Marina V. Shirmankina; Anna V. Krasnopolskaya; Elena I. Naumenko (Педиатрическая фармакология)
varying degrees of risk of life-threatening conditions. Today, the problem of diagnosis and clinical interpretation of EIM in newborns is particularly acute due to anatomical and physiological features and comorbid conditions, as well as in children and adolescents with organic heart diseases. Studying the heterogeneity of electrocardiographic (ECG) morphology of cardiac cycles may have prognostic value for the prevention of arrhythmic events. The article provides an overview of modern scientific data on the signs of EIM in children, including the newborn period, formed into two large groups: depolarization and repolarization disorders. ECG criteria for EIM in children of different ages with congenital (primary) electrical diseases and acquired conditions, including COVID-19, are discussed. The methods of medical correction of ENM in newborns and children in subsequent age periods are highlighted. The totality of the data presented dictates the need for further study of the prognostic significance of EIM and methods of its correction.